Adjunctive effect of compound Kushen Injection to chemotherapy for non-small cell lung cancer: An evidence map and overview of systematic reviews. (5th December 2021) - Yu, Ze-Yu; Peng, Rong-Yan; Han, Mei; Grant, Suzanne; Yang, Guo-Yan; Liu, Jian-Ping; Cao, Hui-Juan
Abstract: Ethnopharmacological relevance: Extract from Kushen ( Sophora flavescens Aiton) and Baituling ( Heterosmilax japonica Kunth), Compound Kushen Injection has a long history for cancer treatment in China. As a common adjunctive drug in chemotherapy of non-small cell lung cancer (NSCLC), the evidence of effectiveness and safety of Compound Kushen Injection needs to be synthesized. Aim of the study: The objective of this overview is to synthesize recent evidence and assess the methodological quality of systematic reviews (SRs) of Compound Kushen Injection, in treating NSCLC as an adjunctive treatment of chemotherapy. Materials and methods: We searched PubMed, PubMed Central, China National Knowledge Infrastructure, Wanfang Data Knowledge Service Platform and VIP China Science and Technology Journal Database from inception to April 22, 2020. We included SRs of the efficacy and safety of Compound Kushen Injection combined with chemotherapy in the treatment of NSCLC. Two authors assessed eligibility and extracted data. The quality of SRs was assessed using AMSTAR-2. A meta-analysis was conducted for the original trials where good homogeneity was present. Evidence maps using bubble plots illustrated overall results. The quality of the evidence was graded by the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach. Results: Twelve SRs were included, with 91 randomized controlled trials and 7466 participants. Overall, the quality of the included SRs was low. Only six SRs reported specific chemotherapy regimens, three using vinorelbine combined with cisplatin (NP), one using paclitaxel combined with cisplatin (TP), one using gemcitabine combined with cisplatin (GP), and one discussed the three regimens in subgroups. Meta-analysis showed that CKI used as an adjuvant to chemotherapy was superior to chemotherapy alone in promoting tumor complete response rate, tumor partial response rate, Kamofsky score, and relieving some chemotherapy related side effects. Evidence mapping showed that Kushen Injection combined with NP and GP had better effect. The evidence quality of increasing Kamofsky score and decreasing the incidence of leukopenia were moderate, others were low or very low. Conclusions: There are some favorable effects in improving short-term effectiveness, quality of life and alleviating some side effects of chemotherapy in patients with NSCLC. Results are more promising when Compound Kushen injection is used as an adjunctive to NP and GP. Promising results are however, compromised by the poor quality overall of the clinical trials. Graphical abstract: Image 1